Asset-Based Community Development in Kampung Mina Mangrove, East Wonorejo, Surabaya as a Community Economic Strengthening Effort - Meirinawati Meirinawati; Tauran Tauran; Fitrotun Niswah; Galih W. Pradana; Suci Megawati (Newinera Publisher, 2021)
The goal of this study is to use the Asset-Based Community Development approach to identify the assets of Kampung Mina Mangrove in Wonorejo. One of the research methods employed is action research using a qualitative approach. Document studies, field surveys, and in-depth interviews are used to collect data, which is then examined inductively and qualitatively. According to research findings, Kampung Mina Mangrove has a relatively high productive age based on human capital with the help of social assets. Mangrove fruit processing is a viable enterprise for the growth of the East Wonorejo area, thanks to strong population and a strategic position. In terms of material assets, the state of the current infrastructure must be considered. From the standpoint of economic assets, SME players will not only wait for financial or capital aid from the government in the future, but will also take the initiative to offer a collaboration or partnership with other business actors who can support each other. From the standpoint of environmental assets, they should pay closer attention to the environmental conditions around eco-tourism sites. East Wonorejo, the village's only access route, must have suitable waste disposal sites and sewers to prevent flooding during the rainy season. Based on the identification of all assets, future expectations are supported, in addition to assistance from different linked parties, so that current SMEs may expand more generally, not just in mangrove regions.